PENGARUH LATIHAN MINI TENIS LAPANGAN TERHADAP HASIL PUKULAN GROUNDSTROKE PADA CLUB TENIS JUNIOR KABUPATEN SUMEDANG - Nurfadila, Resti; Suherman, Ayi; Alif, Muhammad Nur (JURNAL ILMU KEOLAHRAGAAN, 2024)
The purpose of this study was to determine the effect of mini field tennis training on the results of groundstroke strokes in junior tennis club of Sumedang Regency. This type of research is Pseudo-Experimental research, this pseudo-experimental research method uses the One Group Pre-Test Post-Test Design method. The population of this study is all active members of the junior tennis club of Sumedang Regency. The sample in this study used Purposive Sampling consisting of 15 people. The instrument for the test used is the Kemp-Vincent Rally Tennis test to measure the level of strokes in performing a Rally Groundstroke. The data analysis technique uses the Paired-t Test, which is with the intention of comparing the average value of the Pre-Test and Post-Test results before and after treatment with the same sample. Before the Paired-t Test, first test Normality test and Homogeneity test. The results showed that the results of statistical data analysis of the Paired-t Test test obtained p volue (sig.) of (0.001) > (0.05), so there was a significant influence. Thus, it can be concluded that there is an effect of mini field tennis training on the results of groundstroke strokes at the junior tennis club of Sumedang Regency